Determining the Effect of Core Strength Training on Dynamic Balance, Flexibility and Footwork Skill of Badminton Players - Sm, Farooque; Naorem, Sharina; Yumkhaibam, Ahsan Huda; Dhar, Amit; Mitra, Mukesh; Das, Prasanta Kumar (Physical Education Theory and Methodology, 2025)
Background. Badminton is a technical racket sport that requires intense and explosive movements, with performance dependent on factors such as balance, agility, and core strength. Previous research has emphasized the significance of core fitness in fostering stability and dynamic balance for performance and injury prevention. However, its effects on badminton-specific skills remain relatively underexplored. Objectives. This study aimed to investigate the impact of core strength training on dynamic balance, flexibility, and footwork skills among badminton players. Materials and methods. Thirty male intercollegiate badminton players, aged 20-25, were randomly divided into experimental (n = 15) and control (n = 15) groups. Over 12 weeks, the experimental group underwent core strength training, while the control group maintained their regular routine. Pre- and post-test data were collected using the Y-balance test for dynamic balance, sit and reach test for flexibility, and Hick’s footwork skill test for proficiency. Results. Statistical analysis using paired t-tests and ANCOVA revealed significant improvements in the experimental group across all measured parameters, including dynamic balance (anterior, posteromedial, and posterolateral reaches), flexibility, and footwork skills. Conversely, the control group exhibited no substantial changes. Conclusions. These findings underscore the efficacy of core strength training in enhancing essential physical attributes that are critical for badminton performance.